Cave millipeds of the United States. VII. New species and records of the genus Pseudotremia Cope. I. Species from West Virginia, USA (Diplopoda, Chordeumatida, Cleidogonidae) - Shear, William A. (Zootaxa, 2008)
The milliped genus Pseudotremia as it occurs in West Virginia, USA, is reviewed, with new records, mostly from caves. Four new species, Pseudotremia handi, P. kerboi, P. fongi and P. schneiderae are described, for a total known West Virginia fauna of 11 species, though additional species are predicted to occur. Pseudotremia species could be useful model organisms for the study of speciation and phylogeography in cave-dwelling animals.